2022
DOI: 10.1590/1809-4430-eng.agric.v42n6e20220049/2022
|View full text |Cite
|
Sign up to set email alerts
|

Design and Experiment of a Clamp-Holding Precision Maize-Seed-Metering Device

Abstract: To solve the current problems of poor seeding stability and complex maintenance of maize seed-metering devices, a clamp-holding precision maize-seed-metering device is designed. The structure and working principle of the seed-metering device are described, the optimum state of maize seed clamping is analyzed, and the range of each working area of the seed-metering device is determined. The profile and structural parameters of the limit guide plate are designed by analyzing the laws of motion of the seed-pickin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 7 publications
(7 reference statements)
0
29
0
Order By: Relevance
“…In an effort to enhance the performance of hole seeders, numerous scholars have conducted research on metering devices, proposing various structural designs and performance optimizations [32][33][34]. However, research on the seeding process of metering devices remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to enhance the performance of hole seeders, numerous scholars have conducted research on metering devices, proposing various structural designs and performance optimizations [32][33][34]. However, research on the seeding process of metering devices remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…Five levels of factor tests were set up with a gradient of 5 r/min. Each group of tests were repeated 3 times, and the test results were averaged [25][26][27].…”
Section: Simulation Modelmentioning
confidence: 99%
“…In recent years, scholars at home and abroad have conducted a great deal of research on the methods and theories of adjusting the seed suction posture and improving seed mobility. In terms of postural adjustments, Zhang et al [21] designed a hole-slot combination-type hole and clarified the variation rule of rice seed positioning with time, and Chen et al [22] designed an air-aspirated seed discharger with an inclined convex seed extraction structure. The results showed that the single-grain adsorption rate of the convex disk was better than that of the grooved disk and the flat disk.…”
Section: Introductionmentioning
confidence: 99%